ORAL CARE MENSTABILKAN KONDISI FISIOLOGIS NEONATUS RISIKO TINGGI - Fitri Wahyuni. S (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Oral care stables physiological condition in high risk neonates.The incidence of preterm infections in preterm infants is still quite high. Implementation of oral care interventions in preterm infants with high risk has been done as a precaution. The study was conducted using quasi experimental method with 40 newborns with high risk sample, the respondents were divided into two groups, namely the intervention group and the control group, each group of 20 respondents. Data were analyzed using independent t test and wilcoxon. The results of this intervention proved to have beneficial effect can maintain the physiological condition of high risk neonates and avoid deterioration such as oxygen saturation (p value 0.010) and thermoregulation (p value 0.021) which indicated a difference between the control group and intervention group. It is expected that this is a routine therapy program to be performed in the perinatology. Keywords: Breastfeeding, high risk neonates, oral care, physiological condition